Redistributive Policy: A Panacea for Tertiary Education Reform in Nigeria - Kassem, Semshak Danladi; Stephen , Rwang Patrick; Zingdul, Ponmak Kenneth (Kashere Journal of Politics and International Relations, 2025)
The Tertiary Education in Nigeria has faced a lot of challenges over the years, ranging from poor funding, weak infrastructure and the perennial cum incessant ASUU strike. Since 1960 till date, there has been low allocation to the sector as government is allowed to fund education as enshrined in the constitution of the Federal Republic of Nigeria. The authors look at possible ways to seek alternative funding to tertiary education, to enable the ivory towers lived up to their expectations. It was argued that based on current global reality of paucity of funds, government alone can’t fund tertiary education without intervention of wealthy citizens. This postulation is birth out of the necessity to expunged strikes out of the system and brings willing partners in to reduce the burden on government. The paper relied on Secondary source of data collection which focused on sourcing information from library, internet, books, and journals. The article made use of systems theory as theoretical framework to explain how education if properly funded by government and stakeholders would lead to progress and advancement in tertiary sector. It was recommended that, unity of purpose, oneness and collective intervention through redistribution will bring lasting lights in the sector completely.